Evaluation of clinical outcome of laparoscopic hysterectomy versus open abdominal hysterectomy with pelvic lymphadenectomy in endometrial carcinoma early stage - Tawfik, Waleed M.; Sherif, Ahmed F.; Amer, Wagdy M. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: the aim of this study was to compare the operative, post-operative, and the oncological short-term outcomes of laparoscopic hysterectomy with lymphadenectomy and open abdominal hysterectomy with lymphadenectomy for early-stage endometrial cancer. Methods: 80 patients with clinical stage I endometrial cancer were enrolled in this trial; they were divided according to their selection of the method of intervention after counselling into two groups: total laparoscopic hysterectomy with pelvic lymphadenectomy group and total abdominal hysterectomy with pelvic lymphadenectomy group. Results: The mean operative time in the TLH group was 140.85± 10.033 minutes and was 118.45±12.713 minutes in the TAH group (p<0.001). The mean blood loss in the TLH group was 127.5±42.9 ml and 220.5± 84.82 ml in TAH group (p<0.001). The mean duration of postoperative ileus was 12.8±5.022 hours in the TLH group, and it was 22.3±5.573 hours in the TAH group (p<0.001). The mean time of hospital stay in the TLH group was 26.7±5.667 hours and in the TAH group was 116.4± 17.31 hours (p<0.001). Conclusions: Complete surgical staging of endometrial cancer can be performed using laparoscopy as an alternative to routine open method with similar efficacy about nodal retrieval and complication rate, and better operative and postoperative compliance in means of blood loss, ileus and hospital stay which may have an implication on cost saving in the medical service. Lymphadenectomy can be omitted in low-risk cases of endometrial cancer.